Breastfeeding and emerging motherhood identity: An interpretative phenomenological analysis of first time Chinese Australian mothers' breastfeeding experiences. Issue 3 (May 2021) - Kuswara, Konsita; Knight, Tess; Campbell, Karen J; Hesketh, Kylie D; Zheng, Miaobing; Bolton, Kristy A.; Laws, Rachel
Abstract: Background: Chinese Australian mothers are more likely than the general Australian mothers to introduce formula in the first month of age. A better understanding of the context of formula introduction in the early weeks of birth can provide a deeper insight into how Chinese Australian mothers can be supported to continue exclusive breastfeeding. Methods: An interpretative phenomenological analysis approach was used to examine the lived breastfeeding experiences of 11 first time Chinese mothers in Australia. The experiences of those who breastfed exclusively were compared to those who introduced formula in the first month after birth. Findings: An overarching theme across all participants' narratives was the meaning ascribed to breastfeeding in their emerging motherhood identity. Breastfeeding could be a pragmatic and a socially desirable method to nourish an infant but lacking personal identification to the mother. These mothers were more vulnerable to the early introduction of formula, especially when the support environment was lacking. Maternal identity conflict was common and negatively impacted exclusive breastfeeding and mothers' mental health. In contrast, mothers who identified closely with breastfeeding showed greater persistence and enjoyment in breastfeeding and were more likely to continue breastfeeding exclusively. Health professionals were perceived to have an important influence in strengthening maternal breastfeeding motivation and self-efficacy. Conclusion: Breastfeeding support to Chinese Australian mothers needs to consider how breastfeeding can be better integrated with their motherhood identity. Health professionals are well-positioned to facilitate this process through a better understanding of mothers' cultural and social contexts around breastfeeding.